Panorama da indústria brasileira de níquel: contexto internacional, tendências e players - Vilela, Donizeth Alves (2002)
To identify the panorama of the brazilian nickel industry, it was accomplished this descriptive research, using the method of intensive study of some cases. The identifications were done with specific literatures base on nickel and afterwards by means on reports of government organs and of companies. The nickel production is dispersed for the whole planet, which it was elaborated evaluations for geographical distribution and by companies producers of the metal. The obtained results allow to conclude that estimate analysts, regarding production and profitability of the sector are, in fact, positive. However the sector is dependent on sales strategies and russian production, of the stainless steel consumption and stainless steel scrap availability. And, in Brazil as well all over the world are with their hopes torned to the technological innovation denominated HPAL, considered the solution for the profitability increase of the nickel production (and increment of the cobalt production) from the ore laterite, for new investments implementation.